Preparation method of graphene reinforced metal matrix composite material and wire

Through the mixing of modified graphene powder and metal powder and metallurgical sintering of high-temperature and high-pressure powder, graphene reinforced metal-based composite materials are formed, which solves the problem that the mechanical and electrical thermal properties of composite materials are difficult to improve simultaneously in the prior art, and realizes the conductors High strength and high conductivity.

CN119426594APending Publication Date: 2025-02-14SUPER HIGH GUIDANCE TECHNOLOGY (CHENGDU) CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411617195.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-11-17
Filing Date
2024-11-13
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art is difficult to simultaneously improve the mechanical and electrical thermal properties of metal-based composite materials, resulting in the wire being easily blown out and power wasted in high-current applications.

Method used

By modifying the graphene powder into a modified graphene powder, mixing it with the metal powder, ball milling and high-temperature and high-pressure powder metallurgical sintering, a graphene reinforced metal matrix composite material is formed.

Benefits of technology

The tight bonding and density improvement between graphene and metal matrix is ​​achieved, the tensile strength and conductive properties of composite materials are significantly improved, and the problems of burning and power waste of conductors in high-current applications are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119426594A_ABST
    Figure CN119426594A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a graphene reinforced metal-based composite material and a wire, and belongs to the technical field of material preparation. According to the preparation method, the graphene powder and the metal powder are effectively mixed, so that the problems that graphene agglomerates and metal is not easily dispersed are solved, and then the graphene metal composite powder is subjected to continuous extrusion treatment; the continuous powder metallurgy forming process of pure metal powder and graphene metal composite powder can be achieved by regulating and controlling the extrusion technology, tight combination between metal and metal powder and tight combination between metal powder and graphene are achieved, and therefore the potential of high strength and high electric conduction and heat conduction of graphene is effectively exerted. And the comprehensive improvement of the mechanical property and the electric conduction and heat conduction properties of the graphene reinforced metal-based composite material is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material preparation, and in particular relates to a preparation method and a conductor of a graphene-reinforced metal-based composite material. Background Art

[0002] Metals such as copper, aluminum and silver are widely used in the power industry, semiconductor electronics industry, construction and transportation industries due to their excellent electrical conductivity, thermal conductivity, corrosion resistance and plasticity. However, although the resistivity of copper is relatively low (only 6% higher than silver) and the conductivity of aluminum is second only to silver, copper and gold, the inherent resistivity and strength of copper and aluminum are difficult to meet the application requirements of modern industrial technology: on the one hand, the inherent resistivity of copper will generate a large amount of resistance heat. The greater the resistivity of the wire, the greater the resistance and the greater the resistance heat generated. Resistance heat not only causes a large amount of electricity waste, but also requires more electricity to be consumed by the resistance heat of the wire, resulting in the emission of a large amount of carbon dioxide and other gases, which seriously pollutes the environment. In addition, due to a large amount of resistance heat, the temperature of the wire will increase significantly, and even burn the wire, which seriously affects the safety and reliability of the power supply system of the power grid and various electrical appliances. On the other hand, the mechanical strength of pure copper and pure aluminum is low, which cannot meet the needs of some high-power applications. Therefore, it is very important to improve the conductivity and strength of copper and aluminum. However, at present, the improvement of the mechanical strength of copper and aluminum and the improvement of their electrical conductivity are contradictory, that is, when the strength is improved, it often leads to a decrease in conductivity, and it is difficult to improve both at the same time.

[0003] At present, the methods for improving the mechanical and electrical properties of metallic copper mainly include the following: 1. Improving the purity of copper by preparing oxygen-free copper or single crystal copper, thereby reducing the scattering of electrons to improve its conductivity; however, the conductivity of the copper obtained can only be increased by about 8% compared with annealed copper, which is close to the physical upper limit, and is accompanied by a decrease in mechanical properties. 2. Improving the mechanical properties of copper materials by alloying, but the solid solution of alloy elements into the copper matrix will increase the scattering of electrons, thereby causing a decrease in electrical conductivity, that is, there is a strong-conductivity inversion relationship. 3. Preparing copper-based and aluminum-based composite materials by adding carbon nanomaterials (nanocarbon tubes or graphene, etc.) as reinforcements, but due to problems such as the weak interface bonding between graphene and nanocarbon tubes and metals, the strong van der Waals force between graphene and nanocarbon tubes, which leads to easy agglomeration, poor spatial dispersion, and poor interface wettability between carbon materials and copper and aluminum, as well as the density of composite materials and the difficulty of mass production, the comprehensive performance improvement of nanocarbon metal-based composite materials is not ideal and their application is limited. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a preparation method and a conductor of a graphene-reinforced metal-based composite material, so as to solve the technical problem that the mechanical and electrical thermal properties of the composite material cannot be improved at the same time.

[0005] To achieve the above object, the technical solution adopted by the present invention is: to provide a method for preparing a graphene-reinforced metal-based composite material, comprising the following steps: S1, dispersing graphene powder in an organic solvent, then ultrasonicating at a power of 100-600w for 10-30min, then washing and drying, placing the dried product in an acid solution for oxidation for 30-60min, washing and drying, and finally modifying the dried product by physical vapor deposition metal or electrochemical deposition metal to obtain modified graphene powder; S2, mixing the modified graphene powder with the metal powder, wherein the content of the modified graphene powder in the mixed powder is 0.1-30wt%, and then ball milling the mixed powder at a rotation speed of 100-300RPM for 1-3h to obtain a prefabricated composite powder; S3. The prefabricated composite powder is subjected to continuous powder metallurgy sintering, continuous powder extrusion, spark plasma sintering or high-temperature rolling molding to obtain a graphene-reinforced metal-based composite material.

[0006] On the basis of the above technical solution, the present invention can also be improved as follows: Furthermore, the organic solvent is DMF or ethanol.

[0007] Furthermore, the drying temperature is 90-250° C., and the drying time is 1-3 hours.

[0008] Furthermore, the acid solution is a nitric acid solution with a concentration of 1-20wt%.

[0009] Furthermore, the metal powder used in S2 is any one or more of copper, aluminum, and silver.

[0010] The invention also discloses a graphene-reinforced metal-based composite material prepared by the preparation method.

[0011] The invention also discloses a conductive wire comprising the graphene-reinforced metal-based composite material.

[0012] The beneficial effects of the present invention are: 1. The direct contact between graphene is the key factor affecting the inherent performance of graphene, and the agglomeration between graphene is the root cause of the direct contact between them. Due to the nanometer size of graphene, the electrostatic force and van der Waals force between them dominate, which makes graphene easy to agglomerate and difficult to disperse. The present invention wraps graphene by physical deposition and electrochemical deposition of nanometals, such as Figure 2As shown, the metal particles attached to the graphene surface avoid direct contact between the graphene particles, so that the graphene particles are permanently isolated from each other without agglomeration, and a preparation method for uniformly dispersing the modified graphene in copper powder and aluminum powder is achieved through appropriate mixing methods as needed; in addition, the method of the present invention is to carry out wrapping and modification on the complete graphene surface, which will not destroy the integrity and inherent properties of the graphene structure.

[0013] 2. The present invention overcomes the problem of poor wettability between metal and graphene, and achieves doping of graphene, so that free electrons can be easily transferred from the metal (copper, aluminum, etc.) matrix to the graphene, giving full play to the advantage of the ultra-long mean free path of graphene, and significantly improving the conductivity of copper (the conductivity of the metal is proportional to the free electron density and the mean free path. At the interface, it has both the high free electron density of the metal (copper and aluminum) and the ultra-long mean free path of graphene). In addition, high-temperature and high-pressure preparation methods such as continuous powder metallurgy and continuous extrusion form a close bond with the metal (copper and aluminum) matrix at the interface, becoming a stress transfer and electron transfer medium, thereby achieving a joint improvement in strength and conductivity.

[0014] 3. The characteristic of high temperature and high pressure powder metallurgy is that the powder particles can be in close contact under high pressure, and the local melting and recrystallization between the powder particles can be effectively promoted at high temperature, thus effectively solving the problems of the forming and density of the composite material, and is conducive to improving the bonding and density between graphene and the copper matrix, thus contributing to the comprehensive improvement of the mechanical properties of the composite material. At the same time, the number of electrons transferred between graphene and the metal matrix (copper and aluminum, etc.) will increase as the distance between the two decreases. High pressure can effectively reduce the distance between the interfaces of the two. High temperature sintering will maintain the close bonding between the interfaces under high pressure, thereby effectively utilizing the comprehensive characteristics of the high free electron density of metals (copper and aluminum, etc.) and the large mean free path of graphene, taking into account the comprehensive characteristics of close interface bonding and good electron transmission, and achieving the purpose of improving conductivity and strength at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 is the graphene morphology before modification; Figure 2 This is the morphology of the prefabricated composite powder after modification. DETAILED DESCRIPTION

[0016] The specific embodiments of the present invention are described below to facilitate the understanding of the present invention by those skilled in the art. If the specific conditions are not specified in the examples, the methods are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturers are not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially. However, it should be clear that the present invention is not limited to the scope of the specific embodiments. For those skilled in the art, as long as various changes are within the spirit and scope of the present invention defined and determined by the attached claims, these changes are obvious, and all inventions and creations using the concept of the present invention are protected.

[0017] Example 1 A method for preparing a graphene-reinforced metal-based composite material comprises the following steps: S1. 0.2 g of graphene powder was dispersed in 50 mL of DMF, followed by ultrasonic treatment at 600 W for 10 min, then washed with deionized water for 3 times, dried at 90 ° C for 3 h, and the dried product was placed in a 1 wt% nitric acid solution for oxidation for 60 min, washed with deionized water for 5 times, dried at 90 ° C for 3 h, and finally the dried product was subjected to physical vapor deposition of metal to obtain modified graphene powder; S2, 0.5 g of modified graphene powder was mixed with 100 g of aluminum powder, and then the mixed powder was ball-milled at a rotation speed of 100 RPM for 3 h to obtain a prefabricated composite powder; S3. The prefabricated composite powder is sintered by continuous powder metallurgy to obtain a graphene-reinforced metal-based composite material.

[0018] Example 2 A method for preparing a graphene-reinforced metal-based composite material comprises the following steps: S1. 0.2 g of graphene powder was dispersed in 50 mL of ethanol, and then ultrasonicated at 100 W for 30 min, and then washed with deionized water for 5 times, dried at 250 ° C for 1 h, and the dried product was placed in a 20 wt% nitric acid solution for oxidation for 30 min, washed with deionized water for 3 times, and dried at 250 ° C for 1 h, and finally the dried product was modified by electrochemical deposition of metal to obtain modified graphene powder; S2, 0.3 g of modified graphene powder was mixed with 100 g of aluminum powder, and then the mixed powder was ball-milled at a rotation speed of 300 RPM for 1 h to obtain a prefabricated composite powder; S3. The prefabricated composite powder is molded by continuous powder extrusion to obtain a graphene-reinforced metal-based composite material.

[0019] Example 3 A method for preparing a graphene-reinforced metal-based composite material comprises the following steps: S1. 0.5 g of graphene powder (morphology as Figure 1 The graphene was dispersed in 50 mL of ethanol, then ultrasonicated at 350 W for 20 min, washed with deionized water for 4 times, dried at 150 ° C for 2 h, and the dried product was oxidized in a 10 wt% nitric acid solution for 45 min, washed with deionized water for 4 times, dried at 150 ° C for 2 h, and finally the dried product was modified by physical vapor deposition metal to obtain modified graphene powder; S2, 0.3g of modified graphene powder was mixed with 100g of copper powder, and then the mixed powder was ball-milled at a speed of 200RPM for 2h to obtain a prefabricated composite powder; the morphology of the modified graphene was as follows: Figure 2 As shown, it can be seen that nano copper particles are attached to the graphene surface; S3. The prefabricated composite powder is rolled and formed at high temperature to obtain a graphene-reinforced metal-based composite material.

[0020] Experimental example The prefabricated composite powder prepared in step S2 of Example 1-3 was extruded into a line segment with a diameter of 3 mm by a continuous extruder at an extrusion speed of 6 RPM / min to obtain a graphene-enhanced metal-based composite wire. The mechanical properties and electrical conductivity of the wire were tested with reference to GBT4909.3-2009 and GBT3048.2-2007. The mechanical properties test was a standard tensile test with a loading rate of 0.5 N / min. The electrical conductivity test was a standard four-electrode (Kevin method), with current passing through the outer two electrodes and voltage measured through the middle two electrodes, and then the resistivity was calculated. The tensile strength and resistivity data are shown in Table 1.

[0021] Table 1 Comparison of mechanical properties and conductive properties of wires

[0022] It can be seen from the table that compared with pure aluminum wire, the tensile strength of the graphene-enhanced metal-based composite wire prepared by the present invention is increased by 21.56-77.84%, the resistivity is reduced by 3.3-14.34%, and the conductivity is better; compared with pure copper wire, the tensile strength of the graphene-enhanced metal-based composite wire prepared by the present invention is increased by 113%, and the resistivity is reduced by 21.5%, which solves the technical problem that the mechanical and electrical thermal properties of the composite material cannot be improved at the same time.

Claims

1. A method for preparing a graphene-reinforced metal-based composite material, characterized in that: The following steps are involved: S1, dispersing graphene powder in an organic solvent, then ultrasonicating at a power of 100-600w for 10-30min, then washing and drying, placing the dried product in an acid solution for oxidation for 30-60min, washing and drying, and finally modifying the dried product by physical vapor deposition metal or electrochemical deposition metal to obtain modified graphene powder; S2, mixing the modified graphene powder with the metal powder, wherein the content of the modified graphene powder in the mixed powder is 0.1-30wt%, and then ball milling the mixed powder at a rotation speed of 100-300RPM for 1-3h to obtain a prefabricated composite powder; S3. The prefabricated composite powder is subjected to continuous powder metallurgy sintering, continuous powder extrusion, spark plasma sintering or high-temperature rolling molding to obtain a graphene-reinforced metal-based composite material.

2. The method for preparing the graphene-reinforced metal matrix composite material according to claim 1, characterized in that: The organic solvent is DMF or ethanol.

3. The method for preparing the graphene-reinforced metal matrix composite material according to claim 1, characterized in that: The drying temperature is 90-250° C., and the drying time is 1-3 hours.

4. The method for preparing the graphene-reinforced metal matrix composite material according to claim 1, characterized in that: The acid solution is a nitric acid solution with a concentration of 1-20wt%.

5. The method for preparing the graphene-reinforced metal matrix composite material according to claim 1, characterized in that: The metal powder used in S2 is any one or more of copper, aluminum, and silver.

6. A graphene-reinforced metal matrix composite material, characterized in that: The graphene-reinforced metal-based composite material is prepared by the preparation method of any one of claims 1 to 5.

7. A conductor, characterized in that: Including the graphene reinforced metal matrix composite material as described in claim 6.

Citation Information

Cited By

  • Aluminum-based graphene material and preparation method thereof

    CN122327035A